Marketing Strategies in the Intellectual Property Market (Economic journal of Lesya Ukrainka Volyn National University, 2023)
The aim of this work is to investigate and analyze the aspects of the intellectual property market as well as to determine possible marketing strategies for this market. The report also gives a survey of literary sources and legislative acts in the sphere of given research.The article also reveals the essence of such notions as «object of intellectual property», «market of objects of intellectual property». It describes their content and differences from other products, their types and basic implementation of intellectual property rights. The specific features of marketing activities in the process of work with intellectual property are highlighted in this study as well as possible marketing strategies are selected. Based on the research, the conclusion is made that it is reasonable to implement the differentiation strategy in the market of intellectual property. So far, it is suggested the adapted model of differentiation and positioning strategy while entering the market of intellectual property. The value chain is transformed for the intellectual property consumers. Particularly, it is pointed out that this chain should be enlarged with such activities as technological prognostication and forming the ability of intellectual product to ensure the economy of live and materialized labor in the manufacturing process. Special attention is paid to the intellectual property rights management and protection due to the fact that an intellectual product is more inclined to a fast moral ageing than a material one. Finally, the creation of the ability to be sold many times to different customers and in different markets should be added to this value chain. Defining the specific features for positioning the intellectual property objects, such their peculiarities should be taken into consideration as: significance, distinctness, advantage, clearness, copyright protection, simplicity and profitability. This chosen strategy of positioning must have a certain stability, i.e. to stay unchangeable for some period of time, because a quick and frequent change of the strategy imposes an indistinct image. But the market of intellectual property objects is very dynamic. Consequently, the marketing department of a plant should constantly do some market research to investigate these changes and adjust them in the point of positioning strategy.Approaches, suggested in this article, can be put into practice by domestic companies while developing their marketing strategy in the intellectual property market. The aspect for further research is the development of systematic approaches to create the position scheme with distinguishing the segments in the market of intellectual property objects.
Keywords: objects of intellectual property, intellectual property market, marketing strategies, strategy for differentiation and positioning, value chain for the consumers of intellectual properties